An efficient algorithm for fast block matching motion estimation using an adaptive threshold scheme - Kerfa, Djoudi; Saidane, AbdelKader (Multimedia tools and applications, 2020)
A new block-matching algorithm for fast motion estimation is proposed. The so-called Star Diamond Search with Adaptive Threshold ( SD th ) is two steps algorithm. Adaptive threshold for matching errors eliminates invalid blocks early from motion estimation procedure. Then it performs a search for final motion vector with a Star Diamond Algorithm. Proposed SD th algorithm has been implemented and tested using several video sequences. SD th algorithm is also compared with previous search methods to demonstrate its utility.